1997
DOI: 10.2514/2.5218
|View full text |Cite
|
Sign up to set email alerts
|

Jet Engine Component Maps for Performance Modeling and Diagnosis

Abstract: This paper describes an effort to model the performance maps of compressors and turbines (i.e., the relation between mass ow, pressure ratio, and ef ciency), using analytical functions. Analytical functions are tted to the available experimental data using a least-squares-type approach for determining the parameters of the tting function. The success of using a particular function for an application is assessed through a suitably de ned mean error of the model. Apart from presenting the method for setting up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 6 publications
(9 reference statements)
0
18
0
Order By: Relevance
“…This kind of map descriptionpresents the possibility to successfully model maps of different design types. A method of this type has been used by Sieros et al 5 The aim of this study is to describea conceptof modelingthe compressor and turbine characteristics that has been developed specifically for the digital simulation of the transient-state operation of gas-turbine engines. The main innovation is the adaptation of the functions of two variables and original data rescaling.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of map descriptionpresents the possibility to successfully model maps of different design types. A method of this type has been used by Sieros et al 5 The aim of this study is to describea conceptof modelingthe compressor and turbine characteristics that has been developed specifically for the digital simulation of the transient-state operation of gas-turbine engines. The main innovation is the adaptation of the functions of two variables and original data rescaling.…”
Section: Introductionmentioning
confidence: 99%
“…The map for spark advance [29] is highly nonlinear and nonmonotonic and visualization of the surface is critical in the development of control strategies. In [30], Seiros et al model the performance maps of compressors and turbines using analytical functions and also discuss their application to fault diagnosis. In [31], Rizzoni and Guzzella describe methodologies for scaling performance maps for the analysis, design and control of hybrid vehicles.…”
Section: The Need For Performance Mapsmentioning
confidence: 99%
“…Since the Sieros et al model [31] and the Jensen et al model [18] showed relatively bad performances in Fang's study [2], and the Fang and Dai model [2] has a little difficult to conduct fitting procedure because of its extensive computer trial to determine the E, those three models were excluded in the following comparative studies.…”
Section: Comparative Analyses Of the Above Modelsmentioning
confidence: 99%
“…(1) Empirical model Sieros et al [31] introduced a quadratic polynomial expression to approximate the mass flow characteristic,…”
Section: Review Of Turbine Mass Flow Modelsmentioning
confidence: 99%